Effect of dietary supplementation of marigold pigment on immunity, skin and meat color, and growth performance of broiler chickens - Rajput,N (2012)
Marigold flower extract, a natural pigment, was used to determine its effect on carcass and skin pigmentation, immunity and growth performance of broiler chickens. Two hundred and forty 1-day-old Arbor Acres broiler chicks were randomly distributed into four treatment groups with six replicates in a randomized block design. Birds were fed basal diet for 42 d with or without supplementation of marigold flower extract at various concentrations, i.e., 0 (MG0, control), 100 (MG100), 150 (MG150) and 200 (MG200) mg/kg of feed, respectively. Feed intake and live body weight were weekly recorded. Carcass and shank color, and antibody titers against Newcastle and Influenza viruses were measured. Results showed that marigold flower extract significantly (p<0.05) improved live body weight and relative thymus weight. However, feed intake, feed conversion ratio (FCR), and spleen and bursa weights were not significantly affected. Yellowness (b*) of breast and thigh muscles increased by the dietary supplementation of marigold flower extract compared with the control diet. However, lightness (L*), redness (a*) and redness to yellowness ratio (a/b) were not influenced by the treatments. Moreover, Roche color fan scores of the shank skin were increased at market age (d 42). The results revealed that marigold extract enhanced antibody titers against Newcastle and influenza viruses. It was possible to conclude that the dietary supplementation with marigold flower extract at the rate of 200 mg/kg of feed enhanced carcass and shank color, antibody titers against ND and AI, and growth performance of broiler chickens.